Comparison of dopamine D2 receptor (homology model and X-ray structure) and virtual screening protocol validation for the antagonism mechanism - Emanuel Dani Ramdani & , Arry Yanuar, Raymond Rubianto Tjandrawinata (Journal of Applied Pharmaceutical Science, 2019)
The present research work aims to compare the homology model and recent X-ray crystal structure of dopamine D2 receptor (PDB Code: 6CM4) as well as to validate the virtual screening protocol for antagonist compounds. The comparison involved the sequence similarity and the capability of both proteins to produce similar risperidone binding pose with co-crystal structure based on ChemPLP score and Tanimoto Coefficient score generated by PLANTS and Pyplif. Homology model failed to give the correct binding pose as the root mean square deviation fell to >2Å even with similar sequence and folding. Therefore, 6CM4 should be used for virtual screening instead of the homology model. The virtual screening protocol validation of 6CM4 was performed by PLANTS followed by Pyplif filtering. The protocol was able to give EF1% value of 6.238, which was better than the EF1% value of protein dopamine D3 receptor that shared >80% similarity with dopamine D2 receptor. Similarity between the docking pose and the actual pose is considered important to obtain better predictivity.
Keywords: Dopamine D2, 6CM4, homology model, PLANTS, Pyplif.